Executive function and an eight-week sensory-motor training programme in independent-living individuals with Parkinson’s disease. - Puren, Michelle Sharon (Stellenbosch : Stellenbosch University, 2016)
Thesis (M Sport Sc)--Stellenbosch University, 2016